2007
DOI: 10.1007/s10554-007-9261-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial systolic function in noncompaction cardiomyopathy by real-time three-dimensional echocardiography

Abstract: Background Noncompaction cardiomyopathy (NCCM) is a rare disorder with persistance of the embryonic pattern of myoarchitecture. NCCM is characterized by loosened, spongy myocardium associated with a high incidence of systolic and diastolic left ventricular (LV) dysfunction and heart failure (HF). It is known that LV dysfunction contributes to elevated left atrial (LA) and pulmonary vascular pressures, however atrial function has not been examined in NCCM. The objective of the present study was to assess LA sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…MA could be also assessed 'en-face' by RT3DE and was found to be enlarged and functionally impaired in NCCM patients, with a higher incidence and severity of MR (10). LA-EFO was increased in NCCM patients compared to normal individuals suggesting compensating LA work against the dysfunctional LV in NCCM patients (26). 3D-STE-derived LA-EFO of the present NCCM case was in the range previously given by RT3DE (26).…”
Section: Alternative Ways To Assess Left Atrial Function In Noncompacsupporting
confidence: 59%
See 1 more Smart Citation
“…MA could be also assessed 'en-face' by RT3DE and was found to be enlarged and functionally impaired in NCCM patients, with a higher incidence and severity of MR (10). LA-EFO was increased in NCCM patients compared to normal individuals suggesting compensating LA work against the dysfunctional LV in NCCM patients (26). 3D-STE-derived LA-EFO of the present NCCM case was in the range previously given by RT3DE (26).…”
Section: Alternative Ways To Assess Left Atrial Function In Noncompacsupporting
confidence: 59%
“…Because A wave acceleration is relatively constant, it can be approximated as the peak A velocity divided by the time to peak A velocity (25). Using MAD and MAA data, LA-EFO 3D-MAD and LA-EFO 3D-MAA were calculated using the following equation: LAEFO= 0.5×1.06×(MAD 3D or MAA 3D )×V 2 (25,26), where 0.5 is a coefficient factor. LA-EFO 3D-MAD and LAEFO 3D-MAA were 3.8 kdyne and 13.5 kdyne in this case.…”
Section: Comparison Of Three-dimensional Speckle-tracking Echocardiogmentioning
confidence: 99%
“…However, relatively low number of studies are available, in which LA (dys)function was investigated in NCCM. In a recent RT3DE study, LA ejection force was found to be increased in NCCM as compared to controls (13,21).…”
Section: Left Atrial Volumetric and Strain Analysis In Noncompaction mentioning
confidence: 85%
“…LAEFO is based on classic Newtonian mechanics and is a potential useful index for assessing atrial contribution to diastolic performance (28). Over 2D imaging both 3D echocardiographic techniques, RT3DE (14,21,37) and 3DSTE (13) have been demonstrated to be practicable in assessing LAEFO using Doppler-derived mitral inflow A velocity. However, to the best of authors' knowledge this is the first time to examine whether correlations exist between 3DSTE-derived LAEFO and LA volume-based and strain funtional properties respecting cardiac systolic and diastolic functions in healthy subjects.…”
Section: Correlations Between Left Atrial Ejection Force and Left Atrmentioning
confidence: 99%
See 1 more Smart Citation